2014
DOI: 10.1159/000368330
|View full text |Cite|
|
Sign up to set email alerts
|

Taxanes Plus Trastuzumab Compared To Oral Vinorelbine Plus Trastuzumab in HER2-Overexpressing Metastatic Breast Cancer

Abstract: Background: This retrospective analysis was planned as a direct comparison of taxanes plus trastuzumab to the less toxic combination of oral vinorelbine (OV) plus trastuzumab as a first-line therapy for metastatic HER2-positive breast cancer. Patients and Methods: Patients (n = 76) receiving either taxanes (group A) or OV (group B) in combination with trastuzumab were identified from a breast cancer database. Progression-free survival (PFS) was defined as the primary study endpoint; secondary endpoints were ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…Meanwhile, trastuzumab plus vinorelbine or docetaxel (HERNATA) clinical study showed that intravenous vinorelbine (30–35 mg/m 2 on days 1 and 8) combined with trastuzumab has a higher anti-tumor activity than docetaxel plus trastuzumab (TTP 15.3 vs 12.4 months, OS 38.8 vs 35.7 months, respectively) [ 14 ]. A retrospective study compared intravenous taxanes plus trastuzumab to oral vinorelbine (60 mg/m 2 on days 1 and 8 of a 3-week cycle) plus trastuzumab as first-line therapy in HER2-positive metastatic breast cancer patients [ 15 ]. The result showed that the mPFS and mOS were 7 months vs. 9 months (log rank, no significant), 49 months vs. 59 months ( p = 0.033), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, trastuzumab plus vinorelbine or docetaxel (HERNATA) clinical study showed that intravenous vinorelbine (30–35 mg/m 2 on days 1 and 8) combined with trastuzumab has a higher anti-tumor activity than docetaxel plus trastuzumab (TTP 15.3 vs 12.4 months, OS 38.8 vs 35.7 months, respectively) [ 14 ]. A retrospective study compared intravenous taxanes plus trastuzumab to oral vinorelbine (60 mg/m 2 on days 1 and 8 of a 3-week cycle) plus trastuzumab as first-line therapy in HER2-positive metastatic breast cancer patients [ 15 ]. The result showed that the mPFS and mOS were 7 months vs. 9 months (log rank, no significant), 49 months vs. 59 months ( p = 0.033), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Уровень убедительности рекомендаций -B (уровень достоверности доказательств -2) **Трастузумаб 2 мг/кг (нагрузочная доза 4 мг/кг) в/в еженедельно или 6 мг/кг (нагрузочная доза 8 мг/кг в/в в 1-й день каждые 3 нед.) в сочетании с **винорелбином (60 мг/м внутрь в 1-й, 8-й, 15-й дни; начиная с 22-го дня -80 мг/м 1 раз в неделю) [195], [196]. [198].…”
Section: уровень убедительности рекомендаций -B (уровень достоверностunclassified